MASIH RENDAHKAH PARTISIPASI WANITA INDONESIA DALAM PEMBANGUNAN NEGARA ? WHAT INDONESIA LADIES PARTICIPATED DEVELOPING THEIR COUNTRY WAS STILL LAOW ? - -, Priyono - (Joglo, 2004)
ABSTRACT Â Human right or emancipation of men and women in Indonesia is the same. But many applicatings often occur many differences. Because many problems or many factors have affected them. Those many factors i.e : gender problem, the employment, social-culture, etc. Although many womans work professional on the job, namely director of many factories, the head of district, many rectors, many vice rectors or many deans of universities, ministry or president on their country , etc. But now everyone still ask about participating many womans to develop on their country or state development ? Or think still low ? Key words : Human right or emancipation, women participating, state development